Accuracy of bridge span measurements using classical and GNSS methods - Maciejewska, Aleksandra; Brusak, Ivan; Maciuk, Kamil (Budownictwo i Architektura / Civil and Architectural Engineering, 2025)
The primary objective of the authors was to measure the deflection of a bridge span using two different methods and to draw conclusions from the analysis of the results. The Millennium Bridge in Wroclaw was selected as the test object. The bridge was surveyed using both classical geodetic techniques (tacheometry) and a static Global Navigation Satellite System (GNSS) survey. Due to the requirements of both surveying methods, it was necessary to establish a control consisting of five points. Three of these were located on the bridge and were used for displacement measurements, while the other two points were used for control. The article describes the field and office work, considering the measurement process and its analysis. Based on the results, the application of these techniques yielded different values, which influenced their final interpretation. The displacements in the Up, East, and North components are 0.013, 0.011, and 0.032 m by the GNSS technique and 0.002, 0.015, and 0.002 m by tacheometry for the P1, P2, and P3 points, respectively. Furthermore, in the case of the static GNSS measurement, the errors for each displacement did not indicate that any of them was significant according to the three-sigma rule, calculated in relation to the value of each component or point. However, the classical method showed that the displacement at point P2 is significant and is the only one that could have a real impact on the use of the bridge. The result also confirms that a combination of different geodetic technologies, both classical and GNSS, can be effectively used for monitoring cable-stayed bridges.